Fenomena Gerakan Indonesia Tanpa Pacaran Sebagai Kelompok Sub-Culture Aktivisme Keagamaan - Azizah, Rahmalia Wulan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Since its establishment in 2019, the Indonesia Without Dating Movement has been fervently campaigning against the perceived negative consequences of dating and early marriage, positioning it as an absolute solution. La Ode Munafar, the founder and leader, along with the followers of this movement, appear actively engaged in voicing their opinions on the prohibition of dating through social media. The methodology employed involves content analysis of social media publications and coverage from various online media outlets. Recent developments indicate the emergence of controversial subcultural activism within the Indonesia Without Dating Movement, demonstrating symptoms of religious activism. This research reveals several characteristics of subculture within the Indonesia Without Dating Movement, portraying it as a religious activism group. These characteristics include the diffusion network among movement members, a shared identity, the exchange of distinctive meanings, resistance, and marginalization.